Dissecting the role of PfAP2-G in malaria gametocytogenesis - Gabrielle A. Josling (Nature Portfolio, 2020)
The transcription factor PfAP2-G is a key determinant of sexual commitment in Plasmodium falciparum. Here, Josling et al. define the transcriptional regulatory network of PfAP2-G by identifying its DNA binding sites genome-wide, which vary depending on the route of sexual conversion and rely on interactions with the PfAP2-I transcription factor.